2016
DOI: 10.5194/hess-20-2589-2016
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis to objectively appraise drought indicators and model drought impacts

Abstract: Abstract. Drought monitoring and early warning is an important measure to enhance resilience towards drought. While there are numerous operational systems using different drought indicators, there is no consensus on which indicator best represents drought impact occurrence for any given sector. Furthermore, thresholds are widely applied in these indicators but, to date, little empirical evidence exists as to which indicator thresholds trigger impacts on society, the economy, and ecosystems. The main obstacle f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 51 publications
(77 reference statements)
5
101
0
Order By: Relevance
“…Data-driven statistical models have used time series or spatial variability of these impact occurrences as a response variable in regression and classification tree models ( Fig. 6c; Stagge et al, 2015a;Bachmair et al, 2016b;Blauhut et al, 2015). These studies have also shown that impact generation is more complex than previously assumed and may be caused by the cooccurrence of several extremes, lagged effects, and seasonality (Stagge et al, 2015a).…”
Section: Impacts Of Droughtmentioning
confidence: 99%
“…Data-driven statistical models have used time series or spatial variability of these impact occurrences as a response variable in regression and classification tree models ( Fig. 6c; Stagge et al, 2015a;Bachmair et al, 2016b;Blauhut et al, 2015). These studies have also shown that impact generation is more complex than previously assumed and may be caused by the cooccurrence of several extremes, lagged effects, and seasonality (Stagge et al, 2015a).…”
Section: Impacts Of Droughtmentioning
confidence: 99%
“…Other studies have suggested a link between impact severity and the number of records reporting it (e.g. Hernández Varela et al, 2003;Bachmair et al, 2016), but this needs to be taken carefully since the media coverage of a drought event is highly influenced by the sociopolitical context in the affected area (Sonnett et al, 2006;Llasat et al, 2009). A few additional aspects concerning reliability were noticed while processing the records from the press: Accuracy The information on drought occurrence reported in the newspaper may not be accurate.…”
Section: Use Of Impact Records As Drought Referencementioning
confidence: 99%
“…quantitative information) is considered as a benchmark of drought impact on agriculture. The correlation of remote sensing data, especially SPI and NDVI, to agriculture yield data has been widely researched and applied (see Bachmair et al, 2016, for a review). This second type of impact data was included to provide a comparison of the results obtained in the correlation to text-based impact data and results obtained with the most commonly used type of impact data, and discuss the advantages and limitations of one with respect to the other.…”
Section: Benchmarking Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bachmair et al (2016) for instance, found that the accumulation periods of SPI and SPEI best linked to drought impacts vary from one region to the other and also depend on the kind of impact considered. In the Aichfeld example, the SPI6 exhibits the highest correlation with the SGI, suggesting that it is a reasonable indicator for drought impacts on groundwater, in particular pointing to low groundwater levels and thus low aquifer storage and discharge, which might be associated with other adverse environmental or economic effects.…”
Section: And Haas and Birk 2017)mentioning
confidence: 99%